Semantic of Space In Acehnese : Conceptual Metaphor Semantic Cognitive - Ramlan Ramlan; Mulyadi Mulyadi (Sekolah Tinggi Ilmu Al-Qur'an (STIQ) Amuntai Kalimantan Selatan, 2023)
The purpose of this research is to describe the spatial aspects of the spatial conceptualization generated by the dominant metaphors found in Acehnese society both related to Acehnese culture and nature. The author uses Lakoff and Johnson's (1980) cognitive semantic conceptual study which is clarified by Cruse & Croft (2004) and Saeed (2009) in describing and analyzing the data. The concept of space is generated which refers to the container (container) and place (space). Container space includes: (1) inside-out concept, (2) full-empty concept, and (3) content concept. Space includes: (1) up-down concept, (2) center-periphery concept, and left-right image concept. the spatial conceptualization generated by the dominant metaphor found in Acehnese society is divided into three main spaces; seuramoe keue (front porch), rumoh inoeng (tungai porch), and seuramoe likoet (back porch) space related to the container (container) is categorized as the concept of container space in Acehnese houses, while the conceptualization of space related to place is categorized as the concept of space in aceh nature. The metaphor of open space in this element includes the entire open space of open nature in all activities. while the conceptualization of space related to place is categorized as the concept of space in Aceh's realm. The metaphor of open space in this element includes the entire open space of open nature in all activities. while the conceptualization of space related to place is categorized as the concept of space in Aceh's realm. The metaphor of open space in this element includes the entire open space of open nature in all activities.